Zooplankton assemblage of Oyun Reservoir, Offa, Nigeria - K. Mustapha, Moshood (2009)
The influence of physico-chemical properties of Oyun Reservoir, Offa, Nigeria (a shallow tropical African reservoir) on its zooplankton composition and abundance were investigated at three stations for two years between January 2002 and December 2003. Diversity is not high: only three groups of zooplankton were found: Rotifera with eight genera; and Cladocera and Copepoda with three genera each. Rotifera dominated numerically (71.02%), followed by Cladocera (16.45%) and Copepoda (12.53%). The zooplankton was more prevalent during the rainy season, and there were variations in the composition and abundance along the reservoir continuum. Factors such as temperature, nutrients, food availability, shape and hydrodynamics of the reservoir, as well as reproductive strategies of the organisms, strongly influence the generic composition and population density of zooplankton. Prevention of ecological deterioration of the water body would greatly should result in a more productive water body, rich in zooplankton and with better fisheries.